COMBINED TREATMENT FOR EARLY-STAGE ENDOMETRIAL CANCER - V. N. Nechushkina; K Y. Morkhov; V. V. Kuznetsov (Сибирский онкологический журнал)
In spite of number of studies, including randomized, there is lack of consent on adjuvant radiotherapy for early-stage endometrial cancer. The literature and the results of own studies on combined treatment of this pathology are presented in this paper.